DETAILED EXPLORATION OF FUSARIUM SPECIES IN RICE SEEDS FROM BURKINA FASO - Mwangi, Hannah Njeri; Kosgei , Faith Chebet (Ayden Journal of Agriculture and Allied Studies, 2024)
The genus Fusarium is considered as one of the most important groups of plant pathogens distributed in all regions of Burkina Faso. In order to identify the species, molecular characterization of 118 Fusarium single spore isolates was undertaken. The single spore isolates were obtained from 28 populations isolates collected from rice seeds produced in the three main agro-ecological zones of the country. The molecular characterization was done based on the DNA sequence of the 5,8SITS region. The analysis of single spore isolates revealed that 67 isolates (56.78%) belong to the species Fusarium thapsinum, 21 isolates (17.80%) to the species Fusarium equiseti, 20 isolates (16.95%) to the species Fusarium oxysporum and 10 isolates (8.47%) to the species Fusarium chlamydosporum. The phylogenetic tree generated using the UPGMA method showed that isolates of the same species were grouped in the same clade. The present study indicated that among the identified Fusarium species, Fusarium thapsinum is the most widespread on rice seeds. This study is the first report of the exact identity of Fusarium species present in rice seed in Burkina Faso. This information suggests the study of the pathogenicity of these species on rice.